Microwave-assisted drying of Ocimum sanctum leaves: Analysis of moisture content, drying kinetic model, and techno-economics - Heri Septya Kusuma; Destiya Nurul Izzah; Irmanda Wastu Lintu Linggajati (Applied Food Research, 2023)
This study aims to evaluate the drying kinetics of basil leaves using microwave-assisted drying (MAD) to determine moisture content, moisture ratio, drying rate, and economic analysis at various microwave power levels (136, 264, 440, and 616 W). This study discusses the economic analysis between microwave versus oven drying and this study has not been discussed in other studies. The leaves of basil are: 2.83 ± 0.1831 × 1.42 ± 0.1398 cm (small leaves); 4.08 ± 0.1619 × 1.83 ± 0.1059 cm (medium leaves); 6.16 ± 0.1713 × 2.70 ± 0.2357 cm (large leaves). They evaluated each condition using five thin layer models: Henderson and Pabis, Midilli et al., Hii et al., Verma et al., and Diffusion Approximation. Coefficient of correlation (R2), Chi-square (X2), Sum of Square Error (SSE), Root Mean Square Error (RMSE), and Mean Square Error (MSE) were used as the statistical parameters to determine the best drying kinetics model. The results show that the Hii et al. model is the most appropriate. An economic study was conducted between the selected microwave-assisted drying kinetics model and the optimum oven drying conditions from previous research results. Using 17 microwaves resulted in a Rate of Investment (ROI) of 46.9188%, Break Even Point (BEP) of 37.1189%, and interest rate (i) of 0.0094%. While using the 17 ovens resulted in an ROI calculation of 30.5957%, BEP of 43.6197%, and interest rate (i) of 0.0465%. Thus the microwave-assisted drying is more optimum than the oven drying. This research is expected to be useful for industry or further research in food science and the food industry.